Pemanen Air Hujan Dan Hidroponik Kapiler Menuju Pemukiman Sehat Berkelanjutan - martias, indra; Daswito, Rinaldi; Pitriyanti, luh; Jayanti, Vina (Jurnal Salam Sehat Masyarakat (JSSM), 2025)
Climate villages are community-led efforts and methods in response to climate change. The purpose of the community service is to raise awareness of the importance of climate change adaptation and mitigation, and to collect rainwater as a water reserve solution for island communities lacking clean water supplies. Rainwater harvesting is a facility installed to provide water reserves during a clean water crisis, and plans for a hydroponic system can lead to optimal use of yard space to meet family food needs. Implementation methods include practical installation and maintenance. Results of the service include an increase in wastewater treatment plant (IPAH) facilities, an increase in the number of residents collecting and utilizing rainwater, and an increase in the number of island communities utilizing their yard space to meet family food needs. The PPDM program has facilitated the transfer of knowledge and technology, broadened insight, and maximized the potential of natural resources for vegetable cultivation in home gardens. The addition of rainwater harvesting facilities is expected to provide clean water reserves for island residents during the dry season.